2021
DOI: 10.1111/codi.15938
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating variation in enhanced recovery for colorectal surgery: a report from the Surgical Care Outcomes Assessment Program

Abstract: Aim: Robust data demonstrate that enhanced recovery protocols (ERPs) decrease length of stay, complications and cost. However, little is known about the reasons for variation in compliance with ERPs. The aim of this work was to confirm the efficacy of ERPs in a regional network, and to determine factors that are associated with ERP delivery in diverse hospital settings.Method: A prospective cohort of patients was created by recording all elective colorectal operations at hospitals in the Surgical Care Outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Prior work from the SCOAP collaborative showed that MIS colorectal operations were more likely to receive more ERAS components perioperatively, but ERAS implementation had benefits in all operations, especially those with an open approach. 39 A fifth limitation is the lack of information surrounding the conversion of MIS operations to open, including the reason for conversion or at what time in the operation the conversion occurred, as these data are not captured in SCOAP. As such, we cannot tell from our data whether an earlier conversion may have sped up an operation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior work from the SCOAP collaborative showed that MIS colorectal operations were more likely to receive more ERAS components perioperatively, but ERAS implementation had benefits in all operations, especially those with an open approach. 39 A fifth limitation is the lack of information surrounding the conversion of MIS operations to open, including the reason for conversion or at what time in the operation the conversion occurred, as these data are not captured in SCOAP. As such, we cannot tell from our data whether an earlier conversion may have sped up an operation.…”
Section: Discussionmentioning
confidence: 99%
“…Second, each participating hospital was allowed to use their own site-specific ERP which may have impacted postoperative outcomes. Studies have reported an association between the number of ERP components and risk for postoperative complications [ 20 ]. However, it would have been difficult to ask each site to adhere to a uniform ERP, and this was a pragmatic trial.…”
Section: Discussionmentioning
confidence: 99%